Teresa Margolles: mundos - Margolles, Teresa; Uzel, Jean-Philippe; Garcia, Emeren; Zeppetelli, John; St-Gelais, Thérèse; Morales, Lourdes (Musée d'art contemporain de Montréal, 2017)
Violence and the dead are major thematics in the sociopolitical art of Teresa Margolles. Born in Culiacan, Mexico, Margolles unfalteringly exposes the social causes and consequences of the endemic violence that ravages her country: violent deaths from the drug trade, exclusions, feminicides, and social injustice. Many of her works consist of substances or objects that have been in close contact to violent crimes and dead bodies, such as water with which corpses have been cleaned, blood-soaked earth, or fabric drenched in body fluids. This monograph brings together works from the past decade, along with pieces that have never been shown before, including sculptural and photographic installations, performative interventions and videos. Spare, yet powerfully moving, Margolles's work reaches out and brings the viewer into the world of those whose lives have been made invisible.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Décolonisant l'argent à Porto Rico - Negrón-Muntaner, Frances (revue Periferias, 2019)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas--from Nunavut to Tierra del Fuego. Through three themes--landscape, territory, and trade--this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."--Résumé de l'éditeur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé